Harnessing Direct Current Triboelectricity with Dynamic Schottky Diodes on Silicon - Ferrie, Stuart Paul (Curtin University, 2022)
Triboelectric nanogenerators based on moving Schottky diodes are a promising emerging technology for power generation and sensors. This thesis examined a range of systems using atomic force microscopy including pyramidally textured surfaces and a range of monolayer-modified surfaces for their applications in this field. The presence of copper contamination was also studied in these monolayers of interest.